Edukasi Pengolahan Limbah Minyak Jelantah Menjadi Sabun Cuci Di Desa Gebang, Pesawaran, Lampung - Kusuma Handayani; Mohamad Kanedi; Wawan Abdullah Setiawan; Indriyani; Yasmin Fadia (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Cooking oil contains fatty acids made from high-quality vegetable oil so it can be used for environmentally friendly food products. However, repeated heating processes can damage the molecular structure of the oil. So that it can cause several negative impacts such as on health if consumed too often and damage to the ecosystem in the surrounding environment if disposed of carelessly. To overcome these negative impacts, cooking oil waste can be processed into products such as laundry soap. This community service activity was carried out to educate the community, especially those in Gebang Village, Pesawaran Regency, about the dangers of repeated heating of cooking oil, as well as to provide alternatives to process it into more useful products. The results of this community service activity showed an increase in understanding for participants, this can be seen from the increase in the post-test scores worked on by participants and from the results of discussions during the activity.